Impacts of COVID-19 on the Private Sector in Fragile and Conflict-Affected Situations - International Development Association; International Finance Corporation (International Finance Corporation, Washington, DC, 2020)
The Coronavirus (COVID-19) pandemic is having a significant negative impact on the private sector in developing economies, and businesses and individuals in fragile and conflict-affected situations are among the most severely affected. The pandemic has evolved rapidly from a health emergency to a global economic crisis, spreading through the real sector and posing growing risks to financial systems. Notable sector-level impacts include supply and demand-based shocks to infrastructure and private healthcare; disruptions to imports, exports, and global and local value chains; and declining agribusiness activity that threatens food insecurity, all leading to financial sector instability. This note examines these sector-level impacts and provides recommendations for how the development community can address them. It advocates, among other things, for balancing short-term, sector-level relief and restructuring efforts with planning for a medium-term to long-term recovery, leveraging upstream interventions to “Build Back Better,” and collaborating with governments and development partners. As fragile and conflict-affected situations face further pandemic-related setbacks on top of already substantial hardships, it is critical that the global development community prioritize support to these vulnerable populations.